Magneto-Hydrodynamic Darcy-Forchheimer Jeffrey Nanofluid Flow Over a Nonlinear Radially Stretching Sheet with Radiation and Heat Generation/Absorption - Sreehari, P.; C., Srinivas Reddy; Naikoti, Kishan (Discontinuity, Nonlinearity, and Complexity, 2026)
An analysis is executed to study the MHD flow of Jeffrey nanofluid over a nonlinear radial stretching sheet with the influence of thermal radiation and heat generation/absorption. Two more realistic conditions namely convective conditions and zero nanoparticles mass flux condition are applied on the boundary. By applying suitable similarity transformations, the constitutive equation along with energy and concentration equations changed to set of ordinary differential equations. The ODE's(ordinary differential equation) are solved numerically by bvpc4 method. The outcomes are then displayed for numerous values of the physical parameter and discussed. It is obvious that heat transfer rate is noticeably higher for augment Deboray number and friction factor declines with higher values of inertia Coefficient. To validate our obtained outcomes, a comparison in a limiting case is also given and found in excellent agreement.